The impact of thyroid autoimmunity on pregnancy outcomes in women with unexplained infertility undergoing intrauterine insemination: a retrospective single-center cohort study and meta-analysis - Li, Jiaxu; Yu, Jiaxin; Huang, Yingqin; Xie, Baoli; Hu, Qianwen; Ma, Nana; Qin, Rongyan; Luo, Jianxin; Wu, Hao; Liao, Ming; Qin, Aiping (Frontiers in Endocrinology, 2024)
Introduction Infertility affects 8-12% of couples worldwide, with 15-30% classified as unexplained infertility (UI). Thyroid autoimmunity (TAI), the most common autoimmune disorder in women of reproductive age, may impact fertility and pregnancy outcomes. However, the underlying mechanism is unclear. This study focuses on intrauterine insemination (IUI) and its potential association with TAI in UI patients. It is the first meta-analysis following a comprehensive literature review to improve result accuracy and reliability. Methods Retrospective cohort study analyzing 225 women with unexplained infertility, encompassing 542 cycles of IUI treatment. Participants were categorized into TAI+ group (N=47, N= 120 cycles) and TAI- group (N=178, N= 422 cycles). Additionally, a systematic review and meta-analyses following PRISMA guidelines were conducted, incorporating this study and two others up to June 2023, totaling 3428 IUI cycles. Results Analysis revealed no significant difference in independent variables affecting reproductive outcomes. However, comparison based on TAI status showed significantly lower clinical pregnancy rates (OR: 0.43, P= 0.028, 95%CI: 0.20-0.93) and live birth rate (OR: 0.20, P= 0.014, 95%CI: 0.05 ~ 0.71) were significantly lower than TAI- group. There was no significant difference in pregnancy rate between the two groups (OR: 0.61, P= 0.135, 95%CI: 0.32-1.17). However, the meta-analysis combining these findings across studies did not show statistically significant differences in clinical pregnancy rates (OR:0.77, P=0.18, 95%CI: 0.53-1.13) or live birth rates (OR: 0.68, P=0.64, 95%CI: 0.13-3.47) between the TAI+ and TAI- groups. Discussion Our retrospective cohort study found an association between TAI and reduced reproductive outcomes in women undergoing IUI for unexplained infertility. However, the meta-analysis incorporating other studies did not yield statistically significant associations. Caution is required in interpreting the relationship between thyroid autoimmunity and reproductive outcomes. Future studies should consider a broader population and a more rigorous study design to validate these findings. Clinicians dealing with women with unexplained infertility and TAI should be aware of the complexity of this field and the limitations of available evidence.